+0  
 
0
103
4
avatar

3 logx2 + logx18 = 2

 

3p = 9 (27)q

 

log7 - log2 (11q-2p) = 1

 Mar 1, 2020
edited by Guest  Mar 1, 2020
 #1
avatar+30313 
+3

Not clear what you intend the first one to be!  Does it have logx2 or logx(something2) ?

 Mar 1, 2020
edited by Alan  Mar 1, 2020
 #2
avatar
0

logx2

Guest Mar 1, 2020
 #3
avatar+30313 
0

This doesn't have any meaning as written!

Alan  Mar 1, 2020
 #4
avatar+21556 
0

Are your last two equations one problem?

If so:

3p  =  9·(27)q     --->     3p  =  32·(33)q      --->     3p  =  32·(33q)     --->      3p  =  33q + 2     --->     p  =  3q + 2​

 

log27 - log2(11q - 2p)  =  1     --->     log2[ 7 / (11q - 2p) ]  =  1     --->     ​7 / (11q - 2p)  =  21 

                                                                                                     --->     7  =  2( 11q - 2p )      --->     7  =  22q - 4p

Since  p  =  3q + 2     --->     7  =  22q - 4(3q + 2)

                                  --->     7  =  22q - 12q - 8

                                  --->     7  =  10q - 8

                                  --->     15  =  10q      --->     q  = 1.5

 

Substituting:  p  =  6.5

 Mar 1, 2020

6 Online Users

avatar